2018
DOI: 10.1007/s00228-018-2456-y
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of the second-generation direct-acting antivirals (DAAs) in chronic hepatitis C: a register-based study in Sweden

Abstract: PurposeIntroduction of the direct-acting antivirals (DAAs) for treatment of chronic hepatitis C (CHC) infection has been challenging in all health systems. In Sweden, a national protocol for managed introduction was developed. It was optional, but all county councils agreed to implement and follow it. The purpose of this study was to study (a) cure rates among all patients initiated on treatment in 2014–2015, (b) prescribers’ adherence to the drug recommendations and treatment eligibility criteria in the proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…The main reason for this is varying adherence to drug protocol and guidelines for DAAs during the study period from a prescriber's perspective. A Swedish study found that adherence to drug recommendations varied considerably between genotypes and was only moderate after introduction of DAAs, although it increased markedly after 2015[48]. Adherence to DAAs was associated with OAT continuity, and as This is in line with previous studies demonstrating that OAT continuity is a factor for HCV treatment[27].…”
supporting
confidence: 80%
“…The main reason for this is varying adherence to drug protocol and guidelines for DAAs during the study period from a prescriber's perspective. A Swedish study found that adherence to drug recommendations varied considerably between genotypes and was only moderate after introduction of DAAs, although it increased markedly after 2015[48]. Adherence to DAAs was associated with OAT continuity, and as This is in line with previous studies demonstrating that OAT continuity is a factor for HCV treatment[27].…”
supporting
confidence: 80%
“…Regulation (EC) No 726/2004 allows joint regulatory and HTA scientific advice for applicant MAHs at an early stage of development of a medicinal product, and this experience is generally considered positively [81]. However, there is currently a lack of collaboration between medicines regulation and HTA, as well as pricing and reimbursement authorities, in monitoring the effectiveness of new medicines during the post-authorisation phase, although this is increasingly happening at a national level [52,72,[82][83][84][85][86]. With the introduction of conditional approvals, there is a shift in responsibility for effectiveness from the marketing authorisation to the post-authorisation phase [87], and this also brings added burden on the financing of new medicines by national healthcare systems.…”
Section: Consolidation Of Other Relevant Opinions and Recommendationsmentioning
confidence: 99%
“…These new models include encouraging the use of biosimilars and multiple sourced products where pertinent to conserve resources alongside instigating active disinvestment processes (Godman et al, 2014a;WHO, 2015;Parkinson et al, 2015;Guerra-Junior et al, 2017;Moorkens et al, 2017;Godman et al, 2018) as well as a growing use of managed entry agreements (MEAs). However, there are concerns with MEAs including the extent and usefulness of any clinical data collected, as well as the ability to actively monitor the role and value of new medicines in routine clinical care to provide future guidance (Ferrario and Kanavos, 2013;WHO, 2015;Garattini and Curto, 2016;Carlson et al, 2017;Ferrario et al, 2017;Garcia-Doval et al, 2017;Guerra-Junior et al, 2017;Mercer et al, 2017;Eriksson et al, 2018;Frisk et al, 2018;Alvarez-Madrazo et al, 2019;Antonanzas et al, 2019;Mueller et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The first is on the level of healthcare authorities that includes setting strategies for monitoring the use of medicines, second is on the level of healthcare service providers, which for example includes enhancing the use of agreed clinical guidelines, and the third is on the level of medicines used by consumers, which includes raising awareness on key aspects of RUM (World Health Organization, 2012). Whilst these strategies are operational in a number of countries, they are rarely subjected to a thorough assessment of their actual impact in practice such as encouraging the preferential use of multiple sourced medicines where pertinent without compromising care or encouraging caution for new medicines where there are concerns with patient safety (Godman et al, 2010a;Wettermark et al, 2010;Forslund et al, 2011;Kaplan et al, 2012;Moon et al, 2014;Godman et al, 2014b;Troncoso and Diogene, 2014;Frisk et al, 2018;Jacobs et al, 2019). Especially, there seems to be a gap regarding stakeholder engagement to assess the implementation of these strategies, or in gathering information about the key challenges of implementation and ways of circumventing these challenges, w i t h a f o c u s o n v a r i a b l e c o n t e x t s a n d d i ff e r e n t healthcare ecosystems.…”
Section: Introductionmentioning
confidence: 99%